5PSQ-058 Comparative effectiveness of regorafenib versus trifluridine/tipiracil in metastatic colorectal cancer. (2nd March 2018) - Arrieta, M; Lázaro, A; García, C; Rodríguez, P; Ortiz, S; Ferrari, JM
Abstract : Background: Regorafenib and trifluridine/tipiracil (TAS-102) are indicated in metastatic colorectal cancer (mCRC) refractary to standard therapies. Both have been approved after being compared to placebo, so comparative studies with other therapies are needed. Purpose: To compare effectiveness and safety of regorafenib and TAS-102 in patients with advanced mCRC in real clinical practice. Material and methods: A retrospective observational study including all patients with mCRC who started treatment with regorafenib or TAS-102 between February 2013 and May 2017 was carried out. The following variables were collected: sex, KRAS-mutation, age and Eastern Cooperative Oncology Group scale (ECOG) at the beginning of treatment and previous lines. Qualitative and quantitative variables between groups were compared using chi 2 and t-student tests, respectively. Median progression-free survival (PFS) and overall survival (OS) were recorded to evaluate effectiveness. Differences in survival were evaluated with the logrank test. Adverse effects (AEs) classified according to the Common Toxicity Criteria v4.0 and dose reductions were recorded to measure safety. Statistical analysis was carried out using Stata ® 14. Results: Throughout the period of the study 31 patients (41% males, median age 60.7 years, 77% ECOG 1, median previous lines 3.3) started treatment with regorafenib or TAS-102 (10 and 21, respectively). Both groups were comparable in the variables above described. The median PFS and OS in the regorafenib group were 1.77 (0.13–4.36) and 7 (0.03–13.97) months, while in the TAS-102 group these were 2.07 (1.38–3.15) and 7 (5.09–8.91) months. Differences in PFS (p=0.483) and OS (p=0.850) were not statistically significant. The median number of AEs per patient was 4.70 and 2.71 with regorafenib and TAS-102, respectively. Most of them were grade (G) 1–2. The most frequent AEs related to regorafenib were asthaenia (70%, n=7), diarrhoea, hand-foot syndrome, mucositis and hyporexia (30%, n=3), whereas the most common AEs with TAS-102 were asthaenia (42%, n=9), neutropaenia (38%, n=8) and nausea (33%, n=7). Dose reductions were necessary in three patients treated with regorafenib due to infections and asthaenia G3 and in four patients with TAS-102 due to neutropenia G2 (n=2), G3 (n=1) and G4 (n=1). Conclusion: In our study, regorafenib and TAS-102 have similar, modest effectiveness. Differences in toxicity may be decisive in the choice of either treatment. No conflict of interest